2020
DOI: 10.1111/jcmm.15287
|View full text |Cite
|
Sign up to set email alerts
|

Methylation‐mediated miR‐214 regulates proliferation and drug sensitivity of renal cell carcinoma cells through targeting LIVIN

Abstract: LIVIN, a member of the inhibitor of apoptosis proteins (IAPs), is reported playing important roles in the development and progression of multiple human cancers. However, its underlined mechanisms in human renal cell carcinoma (RCC) are still needed to be clarified. In the present study, we reported that inhibition of miR‐214 promoted the expression of LIVIN, then facilitated RCC cells growth and reduced the sensitivity of RCC cells to chemotherapeutic drugs. In constant, overexpression of miR‐214 had contradic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Also, miR-214 has been shown to inhibit proliferation of RCC cells through reduction in expression levels of Insulin-like Growth Factor-1 (IGF-1) Receptor and inhibition of downstream mTORC1 signaling, regardless of VHL status [ 38 ]. Conversely, low expression levels of miR-214 were associated with enhanced cell growth and reduced drug sensitivity in RCC cells [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, miR-214 has been shown to inhibit proliferation of RCC cells through reduction in expression levels of Insulin-like Growth Factor-1 (IGF-1) Receptor and inhibition of downstream mTORC1 signaling, regardless of VHL status [ 38 ]. Conversely, low expression levels of miR-214 were associated with enhanced cell growth and reduced drug sensitivity in RCC cells [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A number of functional studies have revealed deregulated miRNA (either upregulation or downregulation) involved in cell cycle regulation, apoptosis, cell adhesion, and extracellular matrix or metabolism with a key role in RCC [ 111 , 135 , 136 , 137 ]. In this sense, miR-21 is silenced by promoter methylation in RCC, and its expression inhibits RCC growth through regulating LIVIN, a member of the inhibitor of apoptosis proteins [ 138 ].…”
Section: Epigenetics Of Clear Cell Renal Cell Carcinomamentioning
confidence: 99%
“… 8 For instance, miR-214 repressed the growth of renal cell carcinoma cell in vitro and in vivo through targeting LIVIN. 9 Moreover, miR-214-3p was downregulated in hepatocellular carcinoma tissues versus normal liver tissues, and poor miR-214-3p expression was linked to shorter overall survival rate and recurrence-free survival of hepatocellular carcinoma patients. 10 Nevertheless, no researches concentrated on the relevance of miR-214 in CSCC.…”
Section: Introductionmentioning
confidence: 98%